Segregation or Assimilation: Dutch Government Research on Ethnic Minorities in Dutch Cities and its American Frames of Reference - Ruud Janssens (European Journal of American Studies)
While formulating a national policy for ethnic minorities since the 1980s, Dutch government officials interpreted immigrant problems in the cities through American sociological studies. The way the officials defined minorities and immigrant problems as well as their cherry picking of American research contributed to the failure of policy planners to formulate policies to create equality for all Dutch citizens. On the contrary, the officials’ reports increased ethnic conflicts in Dutch society.